Optimalisasi Layanan Pelanggan dan Pemasaran Digital UMKM Handmade Depok - Khusni Faizah; Maylinda Nur Faizah; Felisya Pangi Wijaya; Meli Linda Sari; Mesja Dwika; Sultansyah Adira Putra; Suci Ayu Sudari; Udriyah; Ali Ridho; Nur Fitri Dewi; Alfi Maghfuriyah (Indo Publishing, 2025)
The digital transformation era has significantly changed consumer behavior, demanding faster, more responsive, and accessible services. In response to these shifts, this community service program was conducted in the form of an educational seminar entitled